1994
DOI: 10.1007/bf00374256
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms whereby cytotoxic T lymphocytes damage guinea-pig ventricular myocytes in vitro

Abstract: We studied possible mechanisms whereby cytotoxic T lymphocytes (CTL) damage the myocardium during the immunological rejection of the transplanted heart, by investigating the in vitro interaction between CTL and cardiac myocytes. We utilized the patch-clamp technique to record membrane currents and action potentials from concanavalin A-treated guinea-pig ventricular myocytes conjugated to mouse peritoneal exudate CTL (PEL). PEL-myocyte interaction reduced action potential duration at 50% repolarization (APD50) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
1
12
1
Order By: Relevance
“…Rose and Hill [22] noted at least four possible mechanisms of cardiac damage during the autoimmune process: (1) IL-1-induced nitric oxide; (2) TNF-; (3) cytotoxic CD8 + , and (4) antibodies to cardiac antigens. Of these, in our previous studies we have focused on mechanisms utilized by cytotoxic T lymphocytes (CTL) to bring about myocyte dysfunction [15,37]. Although we have not provided direct proof implicating CTL in the observed electrophysiological perturbations in myocarditis, a large body of evidence indicates that CTL, probably operating via the Fas/ FasL pathway, are key players.…”
Section: Namentioning
confidence: 94%
See 2 more Smart Citations
“…Rose and Hill [22] noted at least four possible mechanisms of cardiac damage during the autoimmune process: (1) IL-1-induced nitric oxide; (2) TNF-; (3) cytotoxic CD8 + , and (4) antibodies to cardiac antigens. Of these, in our previous studies we have focused on mechanisms utilized by cytotoxic T lymphocytes (CTL) to bring about myocyte dysfunction [15,37]. Although we have not provided direct proof implicating CTL in the observed electrophysiological perturbations in myocarditis, a large body of evidence indicates that CTL, probably operating via the Fas/ FasL pathway, are key players.…”
Section: Namentioning
confidence: 94%
“…The notion that the electrophysiological perturbations of diseased myocytes may indeed contribute to the decline in cardiac function, and are not merely 'markers' of heart failure, is indicated by the following observations: (1) direct Fas triggering in isolated myocytes caused electrophysiological perturbations similar, if not identical to those observed in diseased myocytes (see discussion below) [37]. Additionally, we have recently found (unpublished results) that Fas activation by the Fas-antibody Jo2 attenuated I to by 90%, again resembling the findings of the present work.…”
Section: Electrophysiological Alterations In Myocarditismentioning
confidence: 99%
See 1 more Smart Citation
“…More recent work from this group [23,24] has shown that cytotoxic T lymphocytes activated by conconavalin A treatment induce similar changes in isolated adult guinea pig ventricular myocytes. Taken together, these experiments strongly suggest that degranulation of allosensitized cytotoxic T lymphocytes can induce functional changes in target cardiac myocytes and can, in addition, cause myocyte lysis.…”
Section: Effects Of Lymphocytes On Cardiac Myocytesmentioning
confidence: 99%
“…This enables investigation of a variety of functional properties, e.g. electrophysiology, myocyte shortening and intracellular [Ca 2+ ] ([Ca 2+ ] i ) [10,11]. These studies have shown that PEL-myocyte interaction can result in deterioration of action potential characteristics, generation of delayed afterdepolarizations and contracture, eventually leading to destruction of the myocyte.…”
Section: Introductionmentioning
confidence: 99%